2006
DOI: 10.1002/elan.200503440
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunoassay of Human Chorionic Gonadotrophin Based on Its Immobilization in Gold Nanoparticles‐Chitosan Membrane

Abstract: A human chorionic gonadotrophin (hCG) doped gold nanoparticles -chitosan membrane was prepared for forming an immunoconjugate of horseradish peroxidase labeled hCG antibody and hCG on glassy carbon electrode. The nanoparticles provided a congenial environment of the adsorbed proteins. Thus, the immobilized HRP-labeled immunoconjugate showed good enzymatic activity for the oxidation of o-phenylenediamine by H 2 O 2 . With a competitive mechanism, an amperometric method for immunoassay of hCG up to 30 mIU mL À1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…This prepared CEA immunosenor is more economic due to the low-cost ITO film electrode obtained from industrial mass production compared to the method usng a glassy-carbon electrode. 37 It possesses acceptable detection and storage stability for fabrication in batch.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This prepared CEA immunosenor is more economic due to the low-cost ITO film electrode obtained from industrial mass production compared to the method usng a glassy-carbon electrode. 37 It possesses acceptable detection and storage stability for fabrication in batch.…”
Section: Discussionmentioning
confidence: 99%
“…36 It has been extensively used for immunoassay due to the presence of reactive amino and hydroxyl functional groups. 37,38 Since the gold surface permits an easy absorption of protein molecules, colloidal gold nanoparticles have been used as the matrix for the immobilization of antibodies or antigens [39][40][41] in order to retain the bioactivity of macromolecules. It was reported that 3-mercaptopropyl trimethoxysilane has been used to firmly adsorb gold colloids onto functionalized ITO surfaces in the previous studies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the adsorption of colloidal gold nanoparticles in a chitosan membrane (Au-chitosan) could provide a suitable microenvironment similar to the natural environment of bio-conjugates or cells in electrochemical immunoassay. [15][16][17][18][19] Although some studies using Au-chitosan to immobilize antigens on a glassy carbon electrode and carbon-paste electrode have been reported, 13,16,20 an optically transparent and conducting indium-tin oxide (ITO) electrode has never been used for the immobilization of antigen on this membrane to fabricate an electrochemical immunosensor. It was reported that simultaneous immobilization of the mediator and labeled antibody on the electrode surface has been widely used to develop the biosensors.…”
Section: Introductionmentioning
confidence: 99%